Revisiting the empowerment process: linkages between gender equity and nutrition in rural India. - Fivian, Emily. (Tufts University. Tisch Library., 2020)
This presentation focuses on the relationship between inequity in agricultural resources and maternal nutritional outcomes mediated by inequities in decision making and effects of relative inequities between women and men at each stage of the empowerment process.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy